An increasing older population dictates the need to organise palliative care and estabilish hospices - Brkljačić, Morana; Mavrinac, Martina; Sorta-Bilajac, Iva; Bunjevac, Ivan; Čengić, Tomislav; Golubović, Vesna, liječnica; Šustić, Alan (2009)
Abstract: The aim of this study is to assess population needs for the organisation of palliative care and establishment of hospices. An opinion poll was created to investigate these needs. The research was carried out in 2007/2008 among 1564 citizens not working in health services, and 789 health service workers – a total of 2353 people questioned in 7 towns of the Republic of Croatia. The significant results obtained using adequate statistical methods confirm that 90.6% of all respondents favour the introduction of a palliative care system and 88% favour the establishment of hospices. This leads us to conclude that the need to establish a palliative care system and hospices has been recognised by citizens and health service workers, thus their implementation in the Republic of Croatia without further delay should be recommended
Bibliografija: 29 jed
Sažetak
Keywords: Starija populacija -- Palijativna skrb -- Hospicij; Hrvatska